Public perceptions of police efficacy and image: The “fuzziness” of support for the police - Worrall, John L. (American journal of criminal justice, 1999)
Most studies concerning police-community relations have operationalized support for-law enforcement agencies in unidimensional terms. The present study dissects the notion of support for the police into two distinct dimensions: efficacy and image. Efficacy includes perceptions of the police ability to protect citizens, solve crime, and prevent crime. Image includes perceptions of friendliness and fairness of the police. A series of conventional individual-level and contextual variables are modeled in an effort to explore their relative influence on citizen perceptions of police efficacy and image. Data gathered from a national telephone survey of 1,005 citizens reveal that support for local police is both complex and multidimensional. Moreover, the results demonstrate that efficacy and image are independent dimensions, and that each is susceptible to quite different ratings depending upon which independent and dependent variables are modeled.